MicroRNA-30a promotes invasiveness and metastasis in vitro and in vivo through epithelial–mesenchymal transition and results in poor survival of nasopharyngeal carcinoma patients. (July 2014) - Wang, Hai-Yun; Li, Yang-Yang; Fu, Sha; Wang, Xiao-Pai; Huang, Ma-Yan; Zhang, Xiao; Shao, Qiong; Deng, Ling; Zeng, Mu-Sheng; Zeng, Yi-Xin; Shao, Jian-Yong
Although microRNA-30a (miR-30a) has been shown to regulate cancer metastasis, the molecular mechanism has not yet been clearly elucidated in nasopharyngeal carcinoma (NPC). The present study was to investigate the miR-30a expression pattern and its potential functions and further to identify its target gene and corresponding clinical applications in NPC. MiR-30a was identified to be down-regulated in NPC primary tumors compared with metastatic tumors using quantitative real-time PCR. Furthermore, over-expression of miR-30a transfected with precursor increased the ability of metastasis and invasion of NPC tumor cells in vivo and in vitro . E-cadherin was screened as a putative target gene of miR-30a by computational algorithms. Luciferase reporter assays showed that over-expression of miR-30a directly reduced the activity of a luciferase transcript combined with the 3′-untranslated region (3′-UTR) of E-cadherin. Kaplan–Meier survival analysis and log-rank test were analyzed for 1077 NPC patients for overall survival, indicating that a high expression of E-cadherin was beneficial for NPC prognosis ( P = 0.001). Importantly, NPC patients with high expression of E-cadherin had much lower risk of poor prognosis (hazard ratio = 0.757, P = 0.017) using multivariate analysis. In conclusion, miR-30a could play an important role in regulating NPC metastasis and potentially provide useful guidelines for individualized therapy.